2008
DOI: 10.1080/02699050802320132
|View full text |Cite
|
Sign up to set email alerts
|

Prescription medication use in persons many years following traumatic brain injury

Abstract: The research findings indicate a high prevalence of prescription medications in persons with past history of TBI. There is also a high prevalence of anti-convulsants medication use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 17 publications
2
24
1
Order By: Relevance
“…Thus, we are unable to separate the changes in sleep that occur in the months and years following TBI. Psychiatric comorbidities 62 and medication use are also prevalent in TBI, 48 potentially exacerbating sleeping difficulties. Future studies are required to investigate how such factors relate to the risk of sleep disturbance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we are unable to separate the changes in sleep that occur in the months and years following TBI. Psychiatric comorbidities 62 and medication use are also prevalent in TBI, 48 potentially exacerbating sleeping difficulties. Future studies are required to investigate how such factors relate to the risk of sleep disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…47 Individuals with TBI tend to use more medications than the general population, including medications that cross the blood-brain barrier, such as antidepressants. 48 The use of medications may thus contribute to sleep deficits observed in those with TBI. Other secondary complications following TBI, such as medical comorbidities, may also contribute to sleeping difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…1 Masel and DeWitt have proposed that TBI may initiate an ongoing, possibly lifelong, process that affects multiple organ systems and may cause or accelerate the progression of diseases. 10 Chronic diseases that may be attributed to previous TBI in the literature include epilepsy, 11 gradual decline in cognitive function, 12 Alzheimer's disease, 13 Parkinson's disease, 14 hypopituitarism, 15 metabolic dysfunction, 16 and psychiatric diseases (eg, obsessive-compulsive disorder, anxiety disorder, psychotic disorders, and mood disorders). 17 Furthermore, any damage to the brain usually causes impairment to the vascular system, which supplies blood and nutrients to the cells of the brain.…”
mentioning
confidence: 99%
“…Patients with traumatic brain injury are most often prescribed AEDs for post-traumatic seizures, neurobehavioral disorders, and pain. Up to 26% of TBI patients are prescribed these medications chronically after injury, and AEDs are the most frequently prescribed medications in TBI patients under the age of 65 [6].…”
Section: Antiepileptic Drugs For the Treatment Of Acute Traumatic Bramentioning
confidence: 99%
“…Levetiracetam has been used with increasing frequency due to ease of dosing and its role in post-traumatic seizures is still being defined. One trial comparing the effectiveness of levetiracetam versus phenytoin demonstrated no significant difference between the two medications, although there were increased abnormal findings on EEG compared to phenytoin [6] [13].…”
Section: Aeds and Post-traumatic Seizuresmentioning
confidence: 99%